A 60-GHz Ultra-Thin and Flexible Metasurface for Frequency-Selective Wireless Applications - Syeda Fizzah Jilani; Oluyemi P. Falade; Tom Wildsmith; Paul Reip; Akram Alomainy (Applied Sciences, 2019)
This paper demonstrates a design, fabrication and performance evaluation of a frequency selective 60-GHz flexible metasurface in order to facilitate an unobstructed, secure, and low-loss high-frequency signal propagation. The high-attenuation 60 GHz millimeter-wave (MMW) band is selected for the design of a broadband metasurface. The symmetric metasurface unit-cell structure comprises of an assembly of a circular metallic ring embedded with a square-shaped ring. The screen printing process is deployed to perform fabrication of the metasurface on flexible films by means of highly-conductive nanoparticle copper pastes. Electromagnetic (EM) characteristics of the proposed structure are examined by using the quasi-optic bench testing facility in order to validate its potential contribution in the high data-rate communication links. The proposed ultra-thin and flexible metasurface can be integrated on walls and windows as wallpaper to enhance the wireless signal propagation in highly-dense indoor scenarios.